Programa residência pedagógica: um olhar para o percurso formativo de residentes - LIMA, Mariely Layane Almeida de (2020)
This text had as objective to identify in which aspects the actions of the Pedagogical Residency Program of the Mathematical Center/IEMCI/UFPA contributed to the qualification of the educational path of residents of the career of Integrated graduation in Science, Mathematics and Languages. Theoretically, we support Pimenta and Lima (2017), Contreras (2002) and Nóvoa (1995) by discussing aspects of teacher education. Methodologically, we chose to conduct a qualitative and interpretative research, using as instruments of constitution of empirical data, an open questionnaire, available in electronic format, and observations recorded in a field diary. Nineteen interns of the IEMCI / UFPA subproject, who worked in two public schools in Belém-PA, collaborated with the research. Interns show that the experience in the program was relevant to the training, as it provided, among other aspects, the observation, the proposition, the reflection about what was proposed and the elaboration of other intervention proposals.